(untitled) (Legal journal - Research in Legal and Social Sciences, 2024)
The objective of the research is to analyze the mechanisms of control and follow-up, provided by the peace judiciary, in the context of the special procedure for the protection of persons, specifically in the area of domestic and intra-family violence in Cordillera in the period 2023-2024. The research design used for this work is non-experimental, qualitative, phenomenological and hermeneutic, with an explanatory scope. The results showed shortcomings in the control and follow-up system caused by the deficiency in the management of information, as well as a normative insufficiency in the first place, because all the protocols that exist are focused on immediate reaction, but do not have a vision towards the future. In addition, the normative provision that establishes the measure of exclusion from the home requires that it be complemented with the authorization to search homes. Therefore, it is recommended the implementation of an Inter-institutional Follow-up Protocol for the aggressor, containing a re-education program and a normative modification of Law No. 1600/00 on Domestic Violence.